2022
DOI: 10.3390/healthcare10091752
|View full text |Cite
|
Sign up to set email alerts
|

The Style of Coping with Stress, the Health-Related Locus of Control, and the Level of Mindfulness of Patients with Chronic Somatic Diseases in Comparison to Healthy People

Abstract: Background: Psychological factors may be involved in both the development and treatment of somatic diseases. Our study aimed to evaluate the style of coping with stress, health-related locus of control, and level of mindfulness of adult patients with the most common chronic somatic diseases compared with healthy subjects. Methods: 502 chronically ill people were examined (M = 49.27; SD = 14.25), including 288 women and 214 men. The control group consisted of 117 healthy people (M = 45.66; SD = 17.86). The diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The average postoperative mindfulness score of the patients with oral and maxillofacial malignant tumors was 120.28 ± 13.86. In inflammatory bowel disease patients, the mindfulness score was 119.95 ± 8.64 25 . In fibromyalgia patients, the mindfulness score was 131 ± 20.7 26 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The average postoperative mindfulness score of the patients with oral and maxillofacial malignant tumors was 120.28 ± 13.86. In inflammatory bowel disease patients, the mindfulness score was 119.95 ± 8.64 25 . In fibromyalgia patients, the mindfulness score was 131 ± 20.7 26 .…”
Section: Discussionmentioning
confidence: 97%
“…In inflammatory bowel disease patients, the mindfulness score was 119.95 ± 8.64. 25 In fibromyalgia patients, the mindfulness score was 131 ± 20.7. 26 Many studies have shown that mindfulness can be improved through the practice of mindfulness interventions.…”
Section: Discussionmentioning
confidence: 98%
“…This survey's results displayed a positive correlation between confrontation coping and the average score of mindfulness level (r = 0.725, P < 0.05), a negative correlation between avoidance coping and the average score of mindfulness level (r = -0.604, P < 0.05), and a negative correlation between acceptanceresignation coping and the average score of mindfulness level (r = -0.800, P < 0.05). The studies [28,29] have demonstrated that improving patients' positive coping styles and eliminating negative coping can further increase patients' attention to the disease, improve patients' con dence in treatment, encourage patients to focus on the present, and they can adopt positive coping strategies to deal with the negative effects of stress events, thereby improving their level of mindfulness [30].…”
Section: Correlation Between Medical Coping Style and Mindfulness Lev...mentioning
confidence: 99%
“…,2022.) [24] . 4.4 Psychological factors Psychological factors such as low self-esteem, negative thinking patterns, and a history of traumatic life events have been implicated in the development of depression in patients with primary Sjogren's syndrome.…”
Section: Stress and Coping Mechanismsmentioning
confidence: 99%